Current phase 1/2 research for neovascular age-related macular degeneration. Issue 3 (May 2015) - Pecen, Paula E.; Kaiser, Peter K.
<x xml:space="preserve">Abstract</x> Purpose of review The purpose of this review is to provide an update of phase 1 and 2 clinical trials in neovascular age-related macular degeneration that are either currently underway or recently completed by the end of 2014. Recent findings Three gene therapy options are currently in early clinical trials, administered via intravitreal (AAV2-sFLT01) or subretinal (AVA-101 and RetinoStat) injection to express angiogenesis inhibitors. Several eye drops are being developed for topical administration for various angiogenic inhibitors, including regorafenib, squalamine lactate, and PAN-90806. Early development of systemic administration options may be intravenous (iSONEP) or oral (X-82). Initial study of local radiation therapy may be via proton beam irradiation or stereotactic radiotherapy. Several intravitreal injections are being studied including human immuno-conjugate molecule (hl-con1), abicipar pegol, PF582, DE-120, ESBA 1008, and REGN2176-3. Summary Numerous treatment options of neovascular age-related macular degeneration are in phase 1/2 clinical trials including gene therapy, eye drops, systemic dosing, localized irradiation, and various intravitreal injections. Future phase 3 trial results will be observed closely to determine which of these therapies will be the next novel treatment of neovascular age-related macular degeneration.